Chemical composition of lipids from native and exotic fish in reservoirs of the state of Ceará, Brazil - Selene Maia de Morais; Daniela Ribeiro Alves; José Eranildo Teles do Nascimento; Géssica Soares Cavalcante; Franscisco Marcelo Vieira-Araújo (Acta Scientiarum. Animal Sciences, 2016)
Current study analyzes the chemical composition of lipids in fish commonly found in the dams of the state of Ceará, Brazil, namely Pterygoplichthys pardalis (bodó), Hoplias malabaricus (traira), Cichla ocellaris (tucunaré), Prochilodus brevis (curimatã) and Oreochomis niloticus (tilapia). The animals were collected during the summer and Folch extraction procedure was used for the extraction of lipids, whilst Iupac methodology (International Union of Pure and Applied Chemistry [Iupac], 1987) was used to methylate the fatty acids. Methyl esters were analyzed by GC/MS and the different components in fish oil were identified. Palmitic acid, C16:0 (35.71-45.02%), was the saturated fatty acid with the highest percentage, while oleic acid, C18:1Δ9 (10.62-25.29%) had the highest percentage among the unsaturated fatty acids. The chemical composition of analyzed freshwater fish lipids revealed low levels of polyunsaturated fatty acids.